Pengaruh Sosialisasi Produk Digital Terhadap Minat Berlangganan Pada Unit Digital Services PT. Telkom Witel Bandung - Nadia Mayangsari; Widwi Handari Adji (JPEK: Jurnal Pendidikan Ekonomi dan Kewirausahaan, 2023)
This research is motivated by some data that shows the influence of digital product socialization on subscription interest in the Digital Services Unit of PT Telkom Witel Bandung. In this study there is a population of all Indihome loyal customers in Bandung City, with a population of 240 customers and a sample size of 150 customers. The method chosen is a quantitative method using a guttman scale. The data collection technique used is descriptive, namely with survey techniques, namely collecting data through interviews and offering calls. The analysis stage in this study is in the form of data processing using the SPSS application with the results of data analysis test research, using validity test, reliability test, and data analysis using simple linear regression test, coefficient of determination test (R2), and partial (t). This research test proves the results that the socialization carried out by the Digital Services Unit greatly affects the subscription interest of customers. Thus the company must remain consistent in developing this socialization activity, because doing these activities will certainly have a big effect on the future period, namely the company profitability will continue to increase.